2021
DOI: 10.1017/s136898002100344x
|View full text |Cite
|
Sign up to set email alerts
|

Implementing effective salt reduction programs and policies in low- and middle-income countries: learning from retrospective policy analysis in Argentina, Mongolia, South Africa and Vietnam

Abstract: Objective: To understand factors influencing implementation of salt reduction interventions in low- and middle-income countries (LMICs). Design: Retrospective policy analysis based on desk reviews of existing reports and semi-structured stakeholder interviews in four countries, using Walt and Gilson’s ‘Health Policy Triangle’ to assess the role of context, content, process and actors on implementation of salt policy. Setting: Argentina, Mongolia, South Africa and Vietna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 57 publications
0
25
0
Order By: Relevance
“…This is one of the first known studies to examine factors related to the uptake of sodium reduction research into policies and programs in LAC, a topic of interest given the high prevalence of hypertension and CVD, alongside high intakes of sodium in this population. A study conducted a retrospective policy analysis based on reviews of existing reports and semi-structured interviews in 4 LMIC to understand the factors that influenced the implementation of existing salt reduction interventions in each country [ 36 ]. The current study and the policy analysis identified similar factors that impact the research implementation of sodium reduction policies, such as strong leadership and support from the government and other international agencies, as well as adequate resources.…”
Section: Discussionmentioning
confidence: 99%
“…This is one of the first known studies to examine factors related to the uptake of sodium reduction research into policies and programs in LAC, a topic of interest given the high prevalence of hypertension and CVD, alongside high intakes of sodium in this population. A study conducted a retrospective policy analysis based on reviews of existing reports and semi-structured interviews in 4 LMIC to understand the factors that influenced the implementation of existing salt reduction interventions in each country [ 36 ]. The current study and the policy analysis identified similar factors that impact the research implementation of sodium reduction policies, such as strong leadership and support from the government and other international agencies, as well as adequate resources.…”
Section: Discussionmentioning
confidence: 99%
“…For example, since 2015 the Mongolian national salt reduction strategy has been implemented by ‘creating a social, economic and legal environment that supports salt reduction, including by influencing food supply, increasing partnerships between government and relevant stakeholders, and creating an enabling environment to support improved consumer choices’ [ 33 ]. Part of this initiative included training of chefs, students and employees to implement salt reduction in schools, hospitals, workplaces and kindergartens, and voluntary reductions in salt in bread and bakery products agree on with major companies in 2011 [ 34 ]. However, the average daily salt intake in the 15–69 years-old population was 10.5 gr (more than double the WHO recommendation of <5gr) in 2019, which did not much improve compared to the 2013 survey, 11.1 gr in Mongolia [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with previous research on salt-reduction strategies and highlights the need for additional resources and technical support from international organizations. 20 , 21 Developing and implementing nutrition standards for publicly funded institutions in low- and middle-income countries offers an opportunity to prevent the increase in availability of energy-dense and nutrient-poor packaged and processed foods and ensure healthy food environments in institutions. 3 , 4 As a “best-buy” strategy, 18 there is potential for nutrition standards to have a large health and economic impact, provided standards follow core principles of healthy diets (including reducing salt intake), 22 are easily understandable and enforceable, 23 and are successfully implemented by countries.…”
Section: Discussionmentioning
confidence: 99%